Конюшня на Еловой горке. Аня идет в пони-клуб - Ниемеля Реетта (Самокат, 2012)
1-3 кл. Экземпляры: ДО/1 (20131206) / Инвентарный номер: 1 / Цена: 250.00 / Авт.знак: Н 60 / ГРНТИ: 17.82 / ББК: 84.4 (Фин)